Comparative considerations on the epidemiology of Lyme borreliosis and tick-borne encephalitis in Switzerland - Gern, Lise; de Marval, F.; Aeschlimann, André (My University, 1991)
In Switzerland, the spirochete Borrelia burgdorferi and tick-borne encephalitis virus infect the human population. These infections may cause serious pathogenic effects to men and domestic animals. The tick Ixodes ricinus is the vector of both microorganisms. The distribution of the virus is concentrated in small foci scattered in some regions. In these areas, the infection occurs in less than 1 % of the ticks. The distribution of the spirochete is larger and more regular in the Swiss territory and B. burgdorferi is present in 5 to 50 % of/, ricinus. It is the aim of this paper to try to explain how both types of foci occur, considering especially the problem of small mammals as reservoirs for the bacterium and the virus.